Gender wage differences in West Germany: a cohort analysis - Bernd Fitzenberger; Gaby Wunderlich (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
A comprehensive descriptive analysis of gender wage differences over a long time period is missing for West Germany. Using an empirical approach which takes into account explicitely changes of wage distributions for both males and females as well as life-cycle and birth cohort effects, we go beyond conventional decomposition techniques of the average gender wage gap. The paper provides some stylized facts of the level and dynamics of the gender wage gap from 1975 - 1995. The empirical analysis is based upon the IAB-Beschäftigtenstichprobe. Our findings confirm the importance of distributional effects relating to skill level and employment status. While life-cycle wage growth is in general much lower for females compared to males, comparing their estimated time trends implies that the gender wage gap has narrowed substantially in the lower part of the wage distribution especially for low-and medium-skilled females but much less so in the upper part of the wage distribution. Surprisingly, we do not find any cohort effects for wages of female employees.
Keywords: J71; J16; J31; 330; Gender Wage Gap; Quantile Regression; Cohort Analysis; Lohndifferenzierung; Geschlecht; Frauenarbeitslohn; Kohortenanalyse; Schätzung; Deutschland